Oviposition Preferences of the Fall Armyworm (Spodoptera frugiperda) (Lepidoptera: Noctuidae) in Response to Various Potential Repellent and Attractant Plants - Kervin Can; Tsui-Ying Chang; Lekhnath Kafle; Wen-Hua Chen (Insects)
The fall armyworm (FAW), Spodoptera frugiperda, is a major polyphagous pest that mainly feeds on maize and other cash crops. Understanding S. frugiperda’s behavior on different host plants facilitates the development of effective integrated pest management (IPM) plans. Therefore, this study investigated the oviposition preferences of S. frugiperda females among different host plants using no-choice, two-choice, and multiple-choice bioassays. In no-choice bioassays, para grass, Urochloa mutica (Forssk.) (Poales: Poaceae); maize, Zea mays (L.) (Poales: Poaceae); and napier grass, Pennisetum purpureum (Schumach) (Poales: Poaceae) were identified as highly attractive, while sweet sorghum, Sorghum dochna (Forssk.) (Poales: Poaceae); sunhemp, Crotalaria juncea (L.) (Fabales:Fabacea); Egyptian clover, Trifolium alexandrinum (L.) (Fabales:Fabacea); desmodium, Desmodium uncinatum (Jacq.) (Fabales:Fabacea); natal grass, melinis repens (Zizka) (Poales: Poaceae); molasses grass, Melinis minutiflora (P.Beauv.) (Poales: Poaceae); and mung bean, Vigna radiata (R. wilczek) (Fabales: Fabaceae) exhibited reduced oviposition effects. Two-choice bioassays revealed different levels of attractiveness and repellency among different plant combinations. In multiple-choice bioassays, mimicking an intercropping scenario, differences in the number of eggs and egg mass were observed for M:S:D:W (maize, sunhemp, desmodium, and cage wall), S:D:M:W (sunhemp, desmodium, maize, and cage wall), and D:M:S:W (desmodium, maize, sunhemp, and cage wall). This study provides insights into the egg-laying preferences of S. frugiperda females among different host plants, valuable for the management of S. frugiperda. This encourages further research and further identification of novel repellent and attractant host plants, which will ultimately contribute to the development of sustainable and environmentally friendly crop production practices and techniques.